Uma reconfirmação da anistia?: política de estado e o cinema brasileiro dos ano 90 - Oliveira Júnior, José Wandembergue de (2013)
This paper analyzes a group of national films made between 1994 and 2002 whose plot deals with the period of the Brazilian civil-military dictatorship (1964-1985) in dialogue with the Amnesty Act of 1979. Take as a starting point, the hypothesis that there is a common dialogue between the films in relation to the discourse produced in the screens that confirm or refute the position in favor of amnesty "wide, general and unrestricted." For the study is fundamental to consider the ways in which discourses about the dictatorship present in Brazilian cinema produced between 1994 and 2002 relate to its period of production, distribution and consumption as well as realize how movies interact with each other. The films are analyzed taking as its premise the idea that they are important documents for the understanding of their production period, a period of economic and social changes of neoliberal and even changes in the Amnesty Law to increase the scope of the indemnified by State and discussions about the possibility of changing the law to investigate and punish torturers. The films studied bring representations and views that attempt to reconfirm the Amnesty Act and revising it from his characters and the situations they are involved and approaches of military dictatorship.